Peran Social Media Specialist dalam Meningkatkan Kesadaran Peduli Sampah Melalui Instagram @synergynara - Peragi, Aldi; Putri, Wirda Yulita (Innovative: Journal Of Social Science Research, 2025)
Technology has greatly influenced how people communicate and has led to the creation of new professions, such as Social Media Specialists, who play an essential role in connecting organizations with audiences. One example is Nara Synergy, an organization that uses Instagram to actively promote environmental issues, particularly focusing on waste awareness. In Indonesia, waste remains a significant concern, with data showing that approximately 72% of the public lacks sufficient awareness of the issue.This study aims to understand how a Social Media Specialist can utilize Instagram, specifically through @synergynara, to boost waste awareness. The research objective is to examine "The Role of Social Media Specialists in Raising Awareness of Waste Care through Instagram Social Media @synergynara." Using a descriptive qualitative approach, the study collects data through interviews, observations, and documentation. The findings highlight that Social Media Specialists play a crucial role in managing platforms effectively, yet there is room for improvement in the quality and frequency of engagement with the audience. By implementing a more proactive and innovative approach, public understanding of waste issues is likely to increase.Therefore, the Social Media Specialist’s role extends beyond simply managing content; they act as agents of change, inspiring and motivating society toward positive actions for a cleaner environment.